Analisis Pemakaian Alat Pelindung Diri pada Tenaga Kerja Antar-Shift Kerja di PT. Sami Surya Perkasa sebagai Upaya Mengendalikan Risiko di Tempat Kerja - Ivan Dwiyanto; Ayudyah Eka Apsari, Nancy Oktyajati, Sri Mayasari (PROSIDING, 2022)
One of the protection efforts for the workforce is by applying the use of Personal Protective Equipment (PPE) in order to reduce the occurrence of accidents at work. The use of PPE is not considered important, especially for those working in hazardous areas. Even though the use of personal protective equipment is very important for safety at work. The discipline of workers in using PPE is still low, resulting in a large number of work accidents. This study aims to determine the use of Personal Protective Equipment in the company. PT. Sami Surya Perkasa which is engaged in the manufacturing industry. From the data taken through direct observation and interviews with 80 personnel. From the observations made, the percentage of use of PPE in the morning shift and afternoon shift The use of PPE is influenced by factors, namely work shifts and the completeness of existing risk assessments. This research is that the workplace has potential hazards that allow accidents at work, so it is necessary to identify potential hazards. Efforts in controlling risks to the workforce are by applying the use of personal protective equipment so as to create a safe work environment and safety while working is maintained. Kata kunci: Pengendalian risiko; APD; Diagram Fishbone;K3;Shift kerja.